New records and species of Crepidodera Chevrolat (Coleoptera: Chrysomelidae) in Eocene European amber, with a brief review of described fossil beetles from Bitterfeld amber - Bukejs, Andris; Biondi, Maurizio; Alekseev, Vitalii I. (Zootaxa, 2016)
Based on six relatively well-preserved specimens from Eocene Baltic amber, Crepidodera tertiotertiaria sp. nov. is described. The new species is illustrated and compared with morphologically similar extant and fossil relatives. It is the third described fossil species of Crepidodera Chevrolat. In addition to the new taxon, new fossil records of C. decolorata Nadein & Perkovsky from Baltic and Bitterfeld amber are presented. A key to species of Crepidodera described from fossil resins is provided, and a checklist of Coleoptera described from Bitterfeld amber is compiled.